Kenya National Policy Dialogue summary report - Laichena, Joshua; Kiptoo, E.; Nkanyani, S.; Mwamakamba, Sithembile; Jacobs-Mata, Inga; Ires, Idil (International Water Management Institute (IWMI), 2022)
To address the knowledge and coordination gaps and foster an enabling policy and investment environment, the Food, Agriculture and Natural Resources Policy Analysis Network (FANRPAN), together with the International Water Management Institute (IWMI), and the local partner, the Kenya Institute for Public Policy Research and Analysis (KIPPRA) hosted the Kenya National Policy Dialogue at ILRI in Nairobi on 21 November 2022. The dialogue is part of the CGIAR initiative: Diversification and Intensification in East and Southern Africa, launched by CGIAR.